2019
DOI: 10.1111/ocr.12338
|View full text |Cite
|
Sign up to set email alerts
|

Condyle‐glenoid fossa relationship after Herbst appliance treatment during two stages of craniofacial skeletal maturation: A retrospective study

Abstract: Objectives To perform a three‐dimensional evaluation of the position of the condyles in patients treated with Herbst appliance (HA) in two stages of cervical vertebral maturation. Setting and sample population Retrospective case‐control study. Pubertal Herbst group (PHG; n = 24, mean age 14.5 years, CS 3 and CS 4) and pre‐pubertal Herbst group (PPHG; n = 17, mean age 9.9 years, CS 1 and CS 2) were contrasted with comparison groups of non‐orthopaedically treated Class II patients in pubertal (PCG; n = 17, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…CBCT has not been frequently used in the evaluation of condylar response to functional orthopaedic therapy in patients with skeletal Class II malocclusion [ 23 , 24 ]. However, only recently, CBCT was used for the 3D assessment of mandibular and glenoid fossa changes [ 13 , 14 , 25 , 26 ]. It has been demonstrated that CBCT provides accurate and reliable linear measurement of the TMJ dimensions of dry human skulls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CBCT has not been frequently used in the evaluation of condylar response to functional orthopaedic therapy in patients with skeletal Class II malocclusion [ 23 , 24 ]. However, only recently, CBCT was used for the 3D assessment of mandibular and glenoid fossa changes [ 13 , 14 , 25 , 26 ]. It has been demonstrated that CBCT provides accurate and reliable linear measurement of the TMJ dimensions of dry human skulls.…”
Section: Discussionmentioning
confidence: 99%
“…Voudoris et al, have shown condylar anterior condylar displacement following Herbst therapy is stabilized by addition of new bone in posterior aspect of fossa and increased fibrous tissue mass in the posterior aspect of disk [ 35 , 36 ]. The spatial orientation of condyle relatively remains unaffected within the fossa due to minor bone remodelling changes as well as the mechanical drift of condyle into its original position due to soft tissues traction [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of researches showed that after treatment, position of the condyle was more forward and glenoid fossa also remodelled, even in the patients who have anterior disc displacement with reduction [27], treatment-induced deterioration was not found in the disc-condyle relationship compared with pre-treatment, while the relationship was improved in some cases.The research published by Payam Owtad et al [28] found that mandibular advancement can increase FGF8 factor in the TMJ area, which can promote adaptive remodeling of the TMJ disc, but it will cost a relatively long time. Published researches had also reported some biomedical effects of functional mandibular advancement devices on the TMJ, the condyle was migrated to a more anterior position, no considerable stress was investigated on the TMJ structure [9,17,28,29], since TMJ discomfort after MADs wearing might be related to muscle dysfunction rather than pressure on TMJ itself [30,31]. Many researchers also found that adolecence appeared active reconstruction in TMJ area [32,33].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Four of all included studies used MRI to evaluate the morphology and disc-condyle relationship, many researchers [34,35] found patients who received such treatment were more likely to have their temporomandibular joint disc at a more forward position. Paula Loureiro Cheib et al's research [30] indicated that immediately after functional appliance, no signi cant clockwise mandible rotation was observed, on the contrary, the condyles were displaced anteriorly and inferiorly. The systematic review published by Kurt Popowich [17] also supported for the view above that although few patients had their TMJ disc position changed, such changes might cause TMJ discomfort momentarily, but after a period for TMJ to adapt, subjective symptoms and clinical signs seemed to disappear, and no obvious dysfunction was observed in TMJ.…”
Section: Summary Of Evidencementioning
confidence: 99%